Assessment of the microbiological quality of rain water: A case study of selected water scarce area in Bangladesh - Ahmed, Minhaj Uddin; Majumder, Ahmad Kamruzzaman; Hossain, Md Sahadat; Nayeem, Abdullah Al (Stamford Journal of Microbiology, 2019)
Availability as well as access to drinking water is one of the considerable constraints for achieving sustainable goals in many countries while microbial contamination has exacerbated this issue more significantly. The increasing trend of population and industrialization for economic growth has adversely been affecting fresh water resources that eventually leading to scarcity of available drinking water. Hence, controlling water pollution along with focusing on alternative water sources are important for ensuring access to safe drinking water. This study aimed to determine the biological water quality parameters of rainfall water in the water-scarce areas of Bangladesh. About sixty rainwater samples collected from seven different districts were collected for microbial analysis in particular Total Coliform (TC) and Fecal Coliform (FC) by using membrane filtration and direct counting method. The result found that 70 % of samples were free from total coliform, whereas only 5 % samples showed above 100 colonies. On the other hand, 83% samples were free from fecal coliform, whereas only 2% samples were within the range of 11-100 colonies. This study has also revealed that most of the samples collected from Rangamati and Khulna district were free from total coliform and fecal coliform. This study may also encourage people living in these water scarce areas to come forward for rainwater harvesting system as a prospective tool for achieving sustainable goal in drinking sector of Bangladesh. Stamford Journal of Microbiology, Vol.8(1) 2018: 24-26